2016
DOI: 10.1111/bor.12216
|View full text |Cite
|
Sign up to set email alerts
|

Larix during the Mid‐Pleniglacial (Greenland Interstadial 8) on Kotelny Island, northern Siberia

Abstract: Needles, wood and pollen of Larix, recorded in a peat deposit from Kotelny Island, northern Siberia, indicate the local occurrence of larch around 38 000 cal. a BP, which is during the Middle Pleniglacial (Greenland Interstadial 8) of the Weichselian last glacial period. The pollen record, dominated by Cyperaceae, Poaceae, Betula, Alnus, Salix and Artemisia, indicates steppe‐tundra conditions with some shrubs and trees. The distribution of Larix species plays an important role in the reconstruction of climatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…As Larix pollen is generally under-represented in pollen records due to low pollen productivity and low pollen dispersal capacity [ 37 , 96 ], even a single pollen grain is usually accepted as evidence for the local to regional presence of Larix [ 97 ]. Further evidence, that Larix has the potential to grow at such high latitudes and even farther north was provided recently [ 98 ] by Larix wood from Kotelny Island (New Siberian Archipelago) dated to ~38 kyr BP (MIS 3 interstadial). However, in the corresponding time-slice of core L14-02 no Larix sequences were detected.…”
Section: Discussionmentioning
confidence: 99%
“…As Larix pollen is generally under-represented in pollen records due to low pollen productivity and low pollen dispersal capacity [ 37 , 96 ], even a single pollen grain is usually accepted as evidence for the local to regional presence of Larix [ 97 ]. Further evidence, that Larix has the potential to grow at such high latitudes and even farther north was provided recently [ 98 ] by Larix wood from Kotelny Island (New Siberian Archipelago) dated to ~38 kyr BP (MIS 3 interstadial). However, in the corresponding time-slice of core L14-02 no Larix sequences were detected.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in northern Siberia or Canada, there are various lines of evidences (macro-remains, charcoal, DNA, pollen) that trees grew in a periglacial environment just before (e.g. Zazula et al, 2006;B elanger et al, 2014;van Geel et al, 2017), during (Willerslev et al, 2014) or just after the LGM (e.g. Tarasov et al, 2009;Zimmermann et al, 2017).…”
Section: Mountain Tree Refugia and Glacial Firesmentioning
confidence: 99%
“…Indeed, subfossils supported by environmental DNA have demonstrated that trees have survived the LGM in Scandinavia (Kullman, 2008;Parducci et al, 2012) or in Alaska (Brubaker, Anderson, Edwards, & Lozhkin, 2005;Edwards, Armbruster, & Elias, 2014), and grew in periglacial steppes of the upper Pleistocene in central Canada (B elanger, Carcaillet, Padbury, Harvey-Schafer, & Van Rees, 2014) or northern Siberia (van Geel et al, 2017).…”
mentioning
confidence: 99%